Farewell to the laws against torture? The American treatment of detainees in the fight against terrorism - Johannes Thimm (Stiftung Wissenschaft und Politik (SWP), 2005)
Following the nomination of Alberto Gonzales for Attorney General of the United States, the debate about the use of torture in the 'Global War on Terror' has become more intense. Gonzales favors giving the President far-reaching authority in matters concerning the treatment of detainees. His hearing at the Senate provides new insight into the Administration's legal understanding of the meaning of torture. His confirmation by the Senate will allow the existing inhumane treatment of suspects held outside of the US to continue. (SWP-Comments / SWP)
Keywords: 320